COMPARING VOCATIONAL AND TECHNICAL EDUCATION SYSTEM OF TURKEY AND GERMANY - Kurt, Abdulkadir; Köse, Erdoğan (PEOPLE: International Journal of Social Sciences, 2019)
Employing individuals having desired qualifications for required and trained workforce is possible with a sense of qualified vocational and technical education. Vocational and technical education has fallen behind of general academic education in Turkey recently. This situation can be seen as a disadvantage for Turkey who has long term valuable targets to be productive society within the years of 2023 and 2071. So, analysing education system, curriculum and practices of other countries having important success in the field of vocational and technical education is thought to be helpful on explaining the source and reasons of this disadvantage. Germany, which has one of the most employment rate among OECD countries, is selected to be compared with Turkey by different aspects in the context of education system, curriculum and practices in this study. Because of analysing and comparing vocational and technical education system and curriculum of Turkey and Germany, interpretative paradigm, one of the qualitative research methods, was selected as a research method of the study. The findings obtained were discussed with regard to school facilities, curriculum and teacher training system. In this respect, this study is thought to make a great contribution to determine deficiency, activities and required fields on practice.